Implementasi Kebijakan Pembangunan Hutan Tanaman Industri Dalam Meningkatkan Produktivitas Hutan Tanaman Industri di Kabupaten Gorontalo Utara - La Ode Bahtiar (CV. Dalle’ Deceng Abeeayla, 2024)
The aim of this research is to find out how development policies are implemented industrial plantation forests in increasing the productivity of industrial plantation forests in North Gorontalo Regency; what factors hinder the implementation of development policies industrial plantation forests in increasing the productivity of industrial plantation forests in North Gorontalo Regency. This type of research is descriptive with a qualitative approach, where primary data is obtained from interviews and research observations. The main instrument in the research is to see to what extent the implementation of industrial plantation forest development policies can increase the productivity of industrial plantation forests in North Gorontalo Regency, where interviews were conducted from September to November 2016. The results of this research show that there is a need to organize work area boundaries, realize the planting of staple crops and superior plants, administration of forest products and supervision and control. Minimizing inhibiting factors through encroachment on forest areas, land conflicts with local communities and illegal logging.